Collective online platforms for financial and environmental awareness : first international workshop on the Internet for Financial Collective Awareness and Intelligence, IFIN 2016 and first international workshop on Internet and Social Media for Environmental Monitoring, ISEM 2016, Florence, Italy, September 12, 2016 : revised selected papers /: first international workshop on the Internet for Financial Collective Awareness and Intelligence, IFIN 2016 and first international workshop on Internet and Social Media for Environmental Monitoring, ISEM 2016, Florence, Italy, September 12, 2016 : revised selected papers. ([2016]) - Unknown
No abstract available